2022
DOI: 10.1021/acsami.2c13256
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Properties of Transparent Hybrid Coating toward High Hardness, Excellent Flexibility, and Multifunction

Abstract: Transparent functional coatings with glass-like hardness and polymer-like flexibility are highly desirable for flexible and foldable displays. Although several coatings have been developed toward this goal, achieving a functional coating with 9H pencil hardness and extremely low bending radius of curvature (r c) remains a great challenge due to the inherent conflict between hardness and flexibility. To overcome this trade-off, a facile strategy is developed herein. The coating is an organic–inorganic hybrid na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In addition, its critical inward and outward bending diameter could reach 1 mm (Figure I). As shown in Figure , results of some recent studies ,,,,,, and our work on flexible protective coating are plotted in Ashby maps to visualize material properties.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, its critical inward and outward bending diameter could reach 1 mm (Figure I). As shown in Figure , results of some recent studies ,,,,,, and our work on flexible protective coating are plotted in Ashby maps to visualize material properties.…”
Section: Resultsmentioning
confidence: 99%
“…(1) To evaluate the thermal stability in long-term direct exposure to the sunlight, AMTA was sandwiched between two Al plates and placed on a heating stage at 180 °C for 8 h. (2) To mimic the unexpected rainstorm environment, AMTA was rinsed under the high-speed (~6 m/s) water jet for 8 h. (3) Scratch damage test was orthogonally applied onto the AMTA (8×8 cm) surface under a normal load, over a distance of 6 cm at a constant scratch rate of 2 cm/s. Scratch resistance tests 47 were performed in a cyclic reciprocating steel-wool wear apparatus, illustrated in Supplementary Fig. 25a .…”
Section: Methodsmentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxanes (POSS, (R-SiO 1.5 ) n , n = 6, 8, 10, 12, etc. ), are one class of nanosized hybrid nanoblocks of interest in many research areas, including self-organized system-related materials, polymer nanocomposites, and inorganic–organic hybrid functional coatings. With the rigid three-dimensional (3D) configuration, high reactivity, and hybrid nature, , in particular, an intriguing feature of similarity to the secondary building units of zeolites, POSS have also been considered as ideal nanoblocks to develop advanced HPPs. , To date, many studies on the geometry effect of aromatic linking units, such as linear-, planar-, tetrahedral-, propeller-, and ladder-like units, ,, have revealed that the topological combination of POSS with these linking units can tune the porosity and yield various POSS-based porous materials (PPMs) with high performance. However, most studies on PPMs focused on T 8 POSS, and studies on the geometry effect of larger POSS such as T 10 , T 12 , and other compounds are limited (Figure a).…”
Section: Introductionmentioning
confidence: 99%